Повість Петра Волиняка «Михайло Танцюра»: особливості поетики та стилю - Яблонський, Максим; Yablonskyy, Maxym (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано незакінчену повість Петра Волиняка «Михайло Танцюра». Для поетики твору характерні автобіографізм, публіцистичність, виразний антиімперський дискурс. Доведено, що метафоричне мислення, елементи сатири, а також народнорозмовна лексика є важливими засобами в ідеологічних акцентах тексту. In the article it is analyzed the unfinished story of Peter Volyniak «Michailo Tantsyura», including its ideological, artistic and stylistic features. To poetics of work is typical autobiographism, publicistic, marked anti-imperial discourse. It is proved that metaphorical thinking, elements of satire and people’s spoken vocabulary are important means of ideological accents of text. It is emphasized on the social masks and roles of characters (by C. G. Jung). The problem of national identity is considered as one of the main conflict of heroes of the story. It is noted the role of such no plot elements as portrait, dialogue disputation, psychologies landscape. It is traces that intertextuality of work ensured active involvement images of Khvylovy’s short story «Puss in Boots» and the poetry collection of T. Osmachka’s «The fire of scythe». It is also emphasised vivid imagological observations of Peter Volyniak.
The Tale of Peter Volyniak «Michailo Tantsyura»: Features of Poetics and Style
Keywords: література третьої хвилі еміграції; поетика; стиль; публіцистичність; автобіографізм; антиімперський дискурс; інтертекстуальність; імагологія; third wave of emigration literature; poetics; style; publicistic; utobiographism; anti-imperial discourse; intertextuality; imagology